O currículo para a educação infantil: uma leitura da proposta orientada por temas geradores no Projeto Escola Cabana - PENA, Maria Célia Sales (Universidade Federal do Pará, 2011)
The work that I present, deals with elaboration of a research that has as object the boarding of the infantile education in the Projeto Escola Cabana (PEC), developed in the period of 1997 until 2004 in Belém Pará, focusing in its main lens the configuration of the curriculum guided for subjects. To construct on the subject that I explore, I organize the ideas in the field of the critical theoris in education and curriculum, bringing reflections for the infantile education. To study the curriculum for the small child il places as a challenge, therefore the infantile education if became the first platform (not obligator), of the basic education, being currentey obligation of the state its offers to the population.In this situation it is important the discurssion of the curricular proposals that objectify to offer na integral and citizen education for children from o until 6 years. Understanding Escola Cabana wilt this profile I considered myself to make a research directed to the understanding of this proposal in its dimension of resume for infancy being assumed as methodological way to analysis in the documents that make references to specific references in the curriculum, by generating subjects in the infantile education. This way, I problemized, as if configured the curriculum for generating subjects of the PEC, for the infantile and educational and curriculum implication in the procers of formation of social the smale child while subject and of rights. The reading painted us that the configuration of the curriculum for the infantile education in the period of 1997 until 2004, was theoretical way, covered at 3 moments suggesting the following possibilities: at the first configuration of the curriculum for the infantile education in the PEC, was organized from axles of work, coming close itself of the school model, segmenting in areas of knowledges limiting and restrincting the toy as work axle to even do denied too much expressions of the child, being, therefore, still a proposal to exclude the infantile culture. At the second moment, the PEC abandons the organization of the curriculum for work axles and investes in the adhesion of the generating subjects, how ever with few specific references for the infantile education. At the third moment, the PEC invests in meaning of the of the infantile education, prenting the configuration of the curriculum guide for generating subject taking the child and its development as starting point for the curriculum. Therefore, my reading points that with these 3 moments, the PEC was constructed a curricular way for the infantile education, initially being unaware and excluding the children of the popular classes with the infancies and to knowledments, to later inviting them to participate of the infantile education as rights and culture of the child.